Positivity and uniform exponential stability for Volterra integro-dynamical systems on time scales. (August 2021) - Karpuz, Başak; Koyuncuoğlu, Halis Can
Abstract: The main objective of this study is two-fold: First, we provide necessary and sufficient conditions for the positivity of Volterra integro-dynamical systems on time scales by means of Metzler matrices. Secondly, we show that positivity of the system implies uniform exponential stability of the trivial solution under sufficient conditions.